Experimental and modeling study of a membrane filtration process using ceramic membranes to increase retroviral pseudotype vector titer - Nehring, Dirk; Gonzalez, Roberto; Czermak, Peter; Pörtner, Ralf (My University, 2004)
The ability of commercial ceramic asymmetric ultrafiltration membranes with a cut-off of 10 and 20kDa to purify retroviral pseudotype vectors derived from the murine leukemia virus carrying the HIV 1 envelop protein MLV(HIV-1) was studied. To optimize the filtration process a mathematical model of batch wise vector purification was set up. 745 to 1794ml batches of supernatant containing a maximum of 3.2 x 10[superscript]5 colony forming units per ml (cfu/ml) was produced in a 200 ml fixed bed reactor. By cross flow filtration the vector concentration was increased 10-fold with an average recovery of 84.5 ± 4.5 % of the initial infective capacity. Furthermore membrane layer formation and temperature dependent decay of transduction competent vector particles (decay) was included in the mathematical model. A maximal end point titer of 4.1 x 10[superscript]6 cfu/ml was predicted by the model and confirmed reasonably well by experimental data. Transmembrane flow of batch filtration was predicted by solving a set of related differential equations. Our modeling allows scale-up of the process and prediction of process performance including specific issues such as vector degradation.
Keywords: Retrovirus; Gene therapy; Purification; Membrane filtration; Layer formation; Mathematical model; Ceramic membrane